ANALISIS PEMANFAATAN APLIKASI CHATGPT DALAM MENDUKUNG PEMBELAJARAN MANDIRI BERBASIS DIGITAL OLEH SISWA PADA MATA PELAJARAN INFORMATIKA KELAS XI SMA NEGERI 2 BONE - Risma, Risma; Amir, Asmah; Kasmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the increasing use of artificial intelligence technology, particularly ChatGPT, in the learning process, the benefits and impacts of which on students’ self-directed learning are not yet fully understood. This study aims to examine the use of the ChatGPT application in supporting digital-based self-directed learning and to identify the positive and negative impacts of its use by 11th-grade students in the Computer Science course at SMA Negeri 2 Bone. The study employs a qualitative approach with a descriptive research design. The research subjects consist of 11th-grade students who actively use ChatGPT in their Computer Science studies and the subject teacher as a supporting informant. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques, with validity testing conducted through triangulation. The results indicate that students utilize ChatGPT as a digital learning resource to search for information, obtain explanations of course material, complete exercises, deepen their understanding, and support self-directed learning. This use has positive effects, such as easier access to information, improved understanding of the material, more efficient use of study time, and increased student motivation and independence in learning. However, the use of ChatGPT also has negative effects, such as a reliance on instant answers, a decline in critical thinking skills, and the potential to receive inaccurate information if it is not verified. Therefore, ChatGPT should be used wisely as a learning aid, not as a substitute for students’ own thinking processes.